The Galloyl Catechins Contributing to Main Antioxidant Capacity of Tea Made from Camellia sinensis in China - Chunjian Zhao; Chunying Li; Shuaihua Liu; Lei Yang (The Scientific World Journal)
Total polyphenol content, catechins content, and antioxidant capacities of green, dark, oolong, and black teas made from Camellia sinensis in China were evaluated. The total polyphenol content of 20 samples of tea was in the range of 7.82–32.36%. Total catechins content was in the range of 4.34–24.27%. The antioxidant capacity of tea extract was determined by the oxygen radical absorbance capacity (ORAC) test and the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging test. Total polyphenol content, catechins content, and antioxidant capacity decreased in the following order: green > oolong > black > dark tea. A positive correlation existed between the antioxidant capacity and total polyphenol content or catechins content (R2=0.67–0.87). The antioxidant capacities of five major catechins (epigallocatechin gallate (EGCG), epicatechin gallate (ECG), epicatechin, epigallocatechin, and catechin) were determined by online HPLC DPPH radical-scavenging; the antioxidant activity of tea was mainly attributed to the esterified catechins (EGCG or ECG).